Beyond the Crisis: Prospects for Emerging Europe - Zsolt Darvas (Hungarian Academy of Sciences, Institute of Economics, 2011)
This paper assesses the impact of the 2008-09 global financial and economic crisis on the medium-term growth prospects of the countries of central and eastern Europe, the Caucasus and Central Asia, which began an economic transition about two decades ago. We use cross-country growth regressions, putting special emphasis on a proper consideration of the crisis and robustness. We find that the crisis has had a major impact on the within-sample fit of the models used and that the positive impact of EU enlargement on growth is smaller than previous research has shown. The crisis has also altered the future growth prospects of the countries studied, even in the optimistic but unrealistic case of a return to pre-crisis capital inflows and credit booms.
Keywords: C31; C33; O47; 330; crisis; economic growth; growth regressions; transition countries; Finanzkrise; Wirkungsanalyse; Wirtschaftswachstum; Regressionsanalyse; Osteuropa; Kaukasus; Zentralasien